2017
DOI: 10.1007/s00018-017-2684-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulators: multifunctional proteins modulating hypoxia-inducible factor-α protein stability and activity

Abstract: The hypoxia-inducible factor (HIF) is a heterodimeric transcription factor governing a transcriptional program in response to reduced O2 availability in metazoans. It contributes to physiology and pathogenesis of many human diseases through its downstream target genes. Emerging studies have shown that the transcriptional activity of HIF is highly regulated at multiple levels and the epigenetic regulators are essential for HIF-mediated transactivation. In this review, we will discuss the comprehensive regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 109 publications
0
43
0
Order By: Relevance
“…ZMYND8 itself is a HIF-1 and HIF-2 target gene, and thus provides a positive feedback mechanism that amplifies HIFmediated transactivation and subsequent breast cancer progression and metastasis ( Figure 13). Several epigenetic regulators have been shown to coactivate a subset of HIF target genes in cancer cells (7,26,27,43). Our RNA-seq and ChIP-seq data indicate that ZMYND8 co-occupies more than 85% of the genome-wide HIF-1 binding sites and activates more than 60% of the global HIF-dependent coding genes in breast cancer cells, indicating that ZMYND8 also regulates HIF-dependent long noncoding RNAs as they are the direct HIF targets under hypoxia (37).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…ZMYND8 itself is a HIF-1 and HIF-2 target gene, and thus provides a positive feedback mechanism that amplifies HIFmediated transactivation and subsequent breast cancer progression and metastasis ( Figure 13). Several epigenetic regulators have been shown to coactivate a subset of HIF target genes in cancer cells (7,26,27,43). Our RNA-seq and ChIP-seq data indicate that ZMYND8 co-occupies more than 85% of the genome-wide HIF-1 binding sites and activates more than 60% of the global HIF-dependent coding genes in breast cancer cells, indicating that ZMYND8 also regulates HIF-dependent long noncoding RNAs as they are the direct HIF targets under hypoxia (37).…”
Section: Discussionmentioning
confidence: 71%
“…The histone acetyltransferases p300, CBP, and TIP60 induce acetylation of histones H3 and H4 to increase transcription of a subset of HIF-1 target genes (27,28). HDACs 1-7 are also known to enhance or suppress HIF-1 transcriptional activity via the different mechanisms (26). We have demonstrated that JMJD2C demethylates trimethyl lysine 9 of histone H3 at the HREs to increase HIF-1-mediated transactivation in human cancer cells (7).…”
Section: Zmynd8 Acetylation Mediates Hif-dependent Breast Cancer Progmentioning
confidence: 84%
See 1 more Smart Citation
“…Strikingly, loss of KDM5A, whose activity opposes that of KMT2D at H3K4 sites, caused upregulation of hypoxia-responsive genes (37), i.e., an effect opposite to the present KS1-associated suppression of hypoxia response genes, such as Klf10 and Bcl2/adenovirus E1B 19-KD protein-interacting protein 3-like (Bnip3l). Several histone demethylases, and at least 33 chromatin modifiers in total, have been shown to affect hypoxia response genes, 11 of these associating with developmental disorders or cancers, yet KMT2D and other histone methyltransferases have not yet been implicated (38).…”
Section: Discussionmentioning
confidence: 99%
“…2 Our previous studies and others have shown that epigenetic regulators, including writers and erasers, are required for HIF-mediated transactivation. 3 However, how the epigenetic reader modulates HIF transcriptional activity to promote breast tumor progression and metastasis is poorly understood.…”
Section: Hypoxia-inducible Factor; Epigenetic Reader; Gene Regulationmentioning
confidence: 99%